Effect of Four Approaches to Oral Feeding Progression on Clinical Outcomes in Preterm Infants - Rita H. Pickler; Barbara A. Reyna; Paul A. Wetzel; Mary Lewis (Hindawi Limited, 2015)
Background. The purpose of this study of preterm infants was to test the effect of four approaches to the time of transition from gavage to full oral feedings, time to discharge, and weight gain during the transition. Methods. A randomized experimental design was used with four intervention groups: early start (32 weeks' postmenstrual age)/slow progressing experience (gradually increasing oral feedings offered per day); early start/maximum experience (oral feedings offered at every feeding opportunity); late start (34 weeks' postmenstrual age)/slow progressing experience; and late start/maximum experience. Results. The analysis included 86 preterm infants. Once oral feedings were initiated, infants in the late start/maximum experience group achieved full oral feeding and were discharged to home significantly sooner than infants in either early start group. Although not significantly different, these infants also achieved these outcomes sooner than infants in the late start/slow progressing experience group. There were no differences in weight gain across groups. Conclusions. Results suggest starting oral feedings later in preterm infants may result in more rapid transition to full oral feedings and discharge although not at early postnatal ages. Provision of a more consistent approach to oral feeding may support infant neurodevelopment and reduce length of hospitalization.